2009
DOI: 10.2174/1874213000902010062
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of a Fungal Pathogen Promote Pattern Formation in a Tropical Agroecosystem

Abstract: Abstract:Recent studies have shown that the spatial pattern of nests of an arboreal ant, Azteca instabilis (Hymenoptera: Formicidae), in a tropical coffee agroecosystem may emerge through self-organization. The proposed self-organization process involves both local expansion and density-dependent mortality of the ant colonies. We explored a possible mechanism for the density-dependent mortality involving the entomopathogenic fungus Lecanicillium lecanii. L. lecanii attacks a scale insect, Coccus viridis (Cocci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…It could have been the case, as originally suggested [5] that the phorid fly parasitoid was the main agent of control while under the new system either the beetle [9], [18] or the fungal disease [7], [19] may be the culprit. Current evidence is insufficient to favor one or the other, but the change in the nature of the spatial distribution suggests this further mechanistic question.…”
Section: Discussionmentioning
confidence: 99%
“…It could have been the case, as originally suggested [5] that the phorid fly parasitoid was the main agent of control while under the new system either the beetle [9], [18] or the fungal disease [7], [19] may be the culprit. Current evidence is insufficient to favor one or the other, but the change in the nature of the spatial distribution suggests this further mechanistic question.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, total number of scales was estimated at 0 or 50. This census protocol was previously established by other investigators using the same study system and found to have a 93% efficiency (R 2 = 0.926) when compared to direct counting methods (Jackson et al, 2012, Jackson et al, 2009Perfecto and Vandermeer, 2006). Each plant was surveyed in sequential, numerical order.…”
Section: Field Survey Of L Lecanii and A Orbigeramentioning
confidence: 99%
“…For each of these bushes, L. lecanii infection was estimated for the entire bush from 0% to 100% in 5% intervals (Jackson et al, 2012, Jackson et al, 2009. To more accurately census A. orbigera populations, surveys were done about a week after C. viridis and L. lecanii surveys to minimize disturbance to the flying insect community.…”
Section: Field Survey Of L Lecanii and A Orbigeramentioning
confidence: 99%
See 1 more Smart Citation
“…This framework is motivated by the concrete case of the spatial patterning of the arboreal ant Azteca instabilis (Hymenoptera: Formicidae) in a coffee farm in southern Mexico (Perfecto and Vandermeer 2008), and the use of that spatial pattern by its mutualist associate, the green coffee scale Coccus viridis (Hemiptera: Coccidae). The ant, in association with one or more natural enemies, generates a scale‐free distribution of clustered nests in a uniform environment (Vandermeer et al 2008, Jackson et al 2009). Several other populations (beetles, spiders, fungi, in addition to the scale insect itself) become associated with these clusters in a complex fashion (Liere and Perfecto 2008, Livingston et al 2008, Vandermeer et al 2009), with each of the other populations using the clusters of ant nests as basic habitat patches.…”
mentioning
confidence: 99%